Pelatihan Dan Sosialisasi Pembuatan Sabun Padat Organik Dengan Essence Bunga Kenanga - Indrawati, Dwi Wahyu; Ngalalloh, Rizqy Mutawakkil; Setiawan, Moh. Eka; Ananta, Devy Savia (Universitas Muhammadiyah Mataram, 2025)
Abstract: Gajahrejo Village, located in Pasuruan Regency, possesses a variety of natural resources, one of which is the ylang-ylang flower. However, its utilization by the local community remains limited, generally confined to grave visitation rituals or other religious ceremonies. To optimize this potential, a training and outreach program was conducted on the production of organic solid soap using ylang-ylang as the primary ingredient. This Community Service initiative aimed to evaluate the implementation of the program, which is part of the community engagement activities of Universitas Muhammadiyah Sidoarjo. The program was designed to address challenges in creating value-added products based on local resources. The methods employed included practical demonstrations, technical production workshops, and interactive discussions on branding, marketing, and creative packaging design. The primary participants in this program were local members of the Family Welfare Movement (PKK). The results of the program indicated a 75% increase in participants' soft skills and an 80% improvement in hard skills, reflecting the program's success in enhancing the capacity and competence of its participants. This initiative not only promotes individual empowerment but also opens opportunities for developing micro-enterprises based on local potential, serving as a sustainable strategy for strengthening the local economy. Abstrak: Desa Gajahrejo, yang terletak di Kabupaten Pasuruan, memiliki beragam sumber daya alam, salah satunya bunga kenanga. Namun, pemanfaatannya oleh masyarakat setempat masih terbatas, umumnya hanya digunakan untuk keperluan ziarah kubur atau ritual keagamaan lainnya. Untuk mengoptimalkan potensi tersebut, dilaksanakan program pelatihan dan sosialisasi pembuatan sabun padat organik berbahan dasar bunga kenanga. Pengabdian kepada Masyarakat ini bertujuan mengkaji pelaksanaan program yang merupakan bagian dari kegiatan pengabdian masyarakat Universitas Muhammadiyah Sidoarjo. Program ini dirancang untuk mengatasi tantangan dalam menciptakan produk bernilai tambah berbasis sumber daya lokal. Metode yang digunakan meliputi demonstrasi praktis, penyuluhan teknik produksi, serta diskusi interaktif mengenai branding, pemasaran, dan desain kemasan kreatif. Peserta utama dalam program ini adalah ibu-ibu PKK setempat. Hasil kegiatan ini menunjukkan adanya peningkatan softskill peserta sebesar 75% dan peningkatan hardskill hingga 80%, mencerminkan keberhasilan program dalam meningkatkan kapasitas dan kompetensi peserta. Program ini tidak hanya mendorong pemberdayaan individu, tetapi juga membuka peluang pengembangan usaha mikro berbasis potensi lokal, sebagai bagian dari strategi berkelanjutan dalam penguatan ekonomi lokal berbasis potensi daerah.